2010
DOI: 10.1182/blood-2009-06-223719
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived growth factor mediates survival of leukemic large granular lymphocytes via an autocrine regulatory pathway

Abstract: IntroductionLarge granular lymphocyte (LGL) leukemia is a lymphoproliferative disease of either CD3 ϩ cytotoxic T lymphocytes (CTLs) or CD3 Ϫ natural killer cells (NK cells). The majority of LGL patients with T-cell (CD3 ϩ , CD8 ϩ /CD57 ϩ ) or NK-cell (CD3 Ϫ , CD16 ϩ / CD56 ϩ ) leukemia have a clinically indolent course. 1,2 LeukemicLGLs of T-cell phenotype reflect polarized expansion of CD8 ϩ terminal-effector memory cells. 3 Expanded NK cells have an activated phenotype with dysregulated NK receptor expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 33 publications
(52 reference statements)
2
59
0
1
Order By: Relevance
“…IL-15 has been shown to be important for T-cell activation and generation of CD8þ memory cells [12,13]. PDGF is also a master switch controlling leukemic LGL survival [11,14]. This study reinforces the concept that both pro-and anti-activation signals are needed for CTL expansion and persistence [11].…”
supporting
confidence: 71%
“…IL-15 has been shown to be important for T-cell activation and generation of CD8þ memory cells [12,13]. PDGF is also a master switch controlling leukemic LGL survival [11,14]. This study reinforces the concept that both pro-and anti-activation signals are needed for CTL expansion and persistence [11].…”
supporting
confidence: 71%
“…Płytkopochodny czynnik wzrostu jest najsilniejszym czynnikiem wzrostu dla komórek T i NK w białaczce T/NK--LGL. Obok IL-15 odgrywa kluczową rolę w patogenezie w białaczce T-LGL, regulując przeżywal-ność komórek poprzez szlaki sygnałowe PI3K-AKT i MEK/ERK [36].…”
Section: Etiopatogenezaunclassified
“…Our group also found that the activation of PDGFRA is sustained by an autocrine stimulation, a mechanism subsequently found also in T-LGL (ref. 58 and Pileri, personal communication). Notably, PDGFR overexpression was later demonstrated in other T/NK-derived tumors, further strengthening its potential therapeutic relevance (see below) (30).…”
Section: Molecular Pathogenesismentioning
confidence: 99%